Comparative study of compositional viscosity prediction models for medium-heavy oils. (22nd August 2008) - Raut, Bipin; Patil, Shirish L.; Dandekar, Abhijit Y.; Fisk, Robert; Maclean, Beth; Hice, Vanessa
This paper presents a comprehensive comparative study of composition-based Lohrenz-Bray-Clark (LBC) and principle of corresponding states (PCS) class viscosity prediction models for 11 different medium to heavy oils. The data sets span a wide range of pressures from 14.7 psia to 5000 psia; temperatures from 80 F to 180 F; and viscosities from 10 cP to 475 cP, typical of medium to heavy oils. The results show that all the LBC class models heavily underpredict the viscosities, whereas qualitatively PCS class models, in general, predict the viscosities in the range of the experimental values. However, none of the studied models were found to be truly predictive. [Received: June 2, 2007; Accepted: September 21, 2007]